Controlling onion white rot by using Egyptian formulated endo-mycorrhiza (Multi-Vam) - El-Haddad, S.A; Abd El-Megid, M.S.; Shalaby, O.Y (2004)
All tested mycorrhizal treatments to control white rot diseases and increased yield in greenhouse and field., were effective and reduced the diseases infection. Treatment triple No.3 (Application in seed bed 14 days transplanting + Dipping at transplanting time + Soil drench 14 days after transplanting) and treatment single No.5 (Dipping at transplanting time) and treatment double NO.6 (Dipping at transplanting time + Soil drench 14 days after transplanting) were higher root colonization of onion plants. The percentage were 80,73.3 and 73.30/0, respectively. Sporulation were increase with triple treatment No.3 (Application in seed bed 14 days transplanting + Dipping at transplanting time + Soil drench 14 days after transplanting) and double treatment No.2 (Inoculated with Multi VAM in the seed bed 14 days before ransplanting + dipping at transplanting time).
Includes references.
Summary in Arabic.
1
Keywords: White rot (Onions) -- Egypt; Onions -- Diseases and pests; Sclerotium cepivorum -- Control; White-rot fungi